Complexation of Z-ligustilide with hydroxypropyl-β-cyclodextrin to improve stability and oral bioavailability - Lu Yapeng; Liu Siyuan; Zhao Yu; Zhu Li; Yu Shuqin (Acta Pharmaceutica)
To improve the stability and oral bioavailability of Z-ligustilide (LIG), the inclusion complex of LIG with hydroxypropyl- β-cyclodextrin (HP-β-CD) was prepared by the kneading method and characterized by UV-Vis spectroscopy, differential thermal analysis (DTA) and Fourier transform infrared (FTIR) spectroscopy. LIG is capable of forming an inclusion complex with HP-b-CD and the stoichiometry of the complex was 1:1. Stability of the inclusion complex against temperature and light was greatly enhanced compared to that of free LIG. Further, oral bioavailability of LIG and the inclusion complex in rats were studied and the plasma drug concentration-time curves fitted well with the non-compartment model to estimate the absolute bioavailability, which was 7.5 and 35.9 %, respectively. In conclusion, these results show that LIG/HP-β-CD complexation can be of great use for increasing the stability and biological efficacy of LIG